Bufei Jianpi Formula Improves Mitochondrial Function and Suppresses Mitophagy in Skeletal Muscle via the Adenosine Monophosphate-Activated Protein Kinase Pathway in Chronic Obstructive Pulmonary Disease - Mao, Jing; Li, Ya; Feng, Suxiang; Liu, Xuefang; Tian, Yange; Bian, Qingqing; Li, Junzi; Hu, Yuanyuan; Zhang, Lanxi; Ji, Huige; Li, Suyun (Frontiers in Pharmacology, 2020)
Skeletal muscle dysfunction, a striking systemic comorbidity of chronic obstructive pulmonary disease (COPD), is associated with declines in activities of daily living, reductions in health status and prognosis, and increases in mortality. Bufei Jianpi formula (BJF), a traditional Chinese herbal formulation, has been shown to improve skeletal muscle tension and tolerance via inhibition of cellular apoptosis in COPD rat models. This study aimed to investigate the mechanisms by which BJF regulates the adenosine monophosphate-activated protein kinase (AMPK) pathway to improve mitochondrial function and to suppress mitophagy in skeletal muscle cells. Our study showed that BJF repaired lung function and ameliorated pathological impairment in rat lung and skeletal muscle tissues. BJF also improved mitochondrial function and reduced mitophagy via the AMPK signaling pathway in rat skeletal muscle tissue. In vitro, BJF significantly improved cigarette smoke extract-induced mitochondrial functional impairment in L6 skeletal muscle cells through effects on mitochondrial membrane potential, mitochondrial permeability transition pores, adenosine triphosphate production, and mitochondrial respiration. In addition, BJF led to upregulated expression of mitochondrial biogenesis markers, including AMPK-α, PGC-1α, and TFAM and downregulation of mitophagy markers, including LC3B, ULK1, PINK1, and Parkin, with increased expression of downstream markers of the AMPK pathway, including mTOR, PPARγ, and SIRT1. In conclusion, BJF significantly improved skeletal muscle and mitochondrial function in COPD rats and L6 cells by promoting mitochondrial biogenesis and suppressing mitophagy via the AMPK pathway. This study suggests that BJF may have therapeutic potential for prophylaxis and treatment of skeletal muscle dysfunction in patients with COPD.